Cover Image, Volume 28, Issue 10. Issue 10 (21st November 2018) - Sekeres, Melanie J.; Winocur, Gordon; Moscovitch, Morris; Anderson, John A. E.; Pishdadian, Sara; Martin Wojtowicz, J.; St‐Laurent, Marie; McAndrews, Mary Pat; Grady, Cheryl L.
Abstract : Cover legend: This cover image is based on the Research Article Changes in patterns of neural activity underlie a time‐dependent transformation of memory in rats and humans by Melanie J. Sekeres et al., DOI:10.1002/hipo.23009 .